2020
DOI: 10.1080/1828051x.2020.1822763
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dietary supplementation of nanoparticles-chromium, chromium-methionine and zinc-proteinate, on performance of Japanese quail under physiological stress

Abstract: The effects of dietary Nanoparticles-Chromium, Chromium methionine, and Zinc-proteinate on performance, blood characteristics and meat quality of physiologically stressed quails were studied. The stress was induced by adding dexamethasone (0.6 mg/kg BW) to diet when quails were between 17 and 22 days of age. Three hundred one-day chicks were randomly assigned to five groups comprising four replicates of 15 birds: negative control diet (no-stress, no-additive), positive control diet (stress, no-additive), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Different Zn sources did not have any significant effects on live weights. The findings of this study agree with the results of previous studies conducted with Zn supplementations (Barzegar et al, 2020; Cufadar et al, 2020; Sahin et al, 2005; Sevim & Olgun, 2021; Zhao et al, 2014). Reda et al (2021) indicated that biological nano‐mineral increased live weights.…”
Section: Discussionsupporting
confidence: 93%
“…Different Zn sources did not have any significant effects on live weights. The findings of this study agree with the results of previous studies conducted with Zn supplementations (Barzegar et al, 2020; Cufadar et al, 2020; Sahin et al, 2005; Sevim & Olgun, 2021; Zhao et al, 2014). Reda et al (2021) indicated that biological nano‐mineral increased live weights.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in quail broilers, supplementation of nano-Cr at 800 µg/kg diet was effective in reducing the negative effects of physiological stress induced by dexamethazone. The performance and hematological parameters were not affected with nanoparticles-chromium, but they increased meat oxidative stability in stressed birds by reducing malondialdehyde concentration in the thigh muscle (Yarmohammadi et al 2020 ). Neither the growth performance of birds nor the rate of egg production was affected by supplementation of chromium nanoparticles.…”
Section: Metal Nanoparticles In the Nutrition Of Particular Animal Sp...mentioning
confidence: 99%
“…By increasing nanoparticle surface area, nanoparticles have the potential to interact efficiently with the body, and their increased retention time in the gut and the reduction of intestinal clearance mechanisms may result in improved bioavailability and function [7]. Thus, nanoparticles can improve growth performance, meat quality, digestion and metabolic or antioxidant enzymes, and mineral content in different tissues under physiological stress [8]. In the poultry industry, nanoparticles smaller than 100 nanometers, such as Ag, Se, Cu, Zn, and others, have been used [6,7,9].…”
Section: Introductionmentioning
confidence: 99%